Future Computers: Digital, Quantum, Biological. - Treleaven, Philip (Computer (00189162), 2021)
Quantum computers offer huge potential performance, and biological computers can revolutionize pharmaceuticals. However, simple "engineering" descriptions and standardized approaches are needed. We provide "layperson" descriptions of quantum and biological computer architectures, comparisons with digital computers, and discussions of industry-standard models.